A cytotoxicity and sub-acute toxicity study on tea leaves cultivated in Sabah - Mohd Noor, Nor Qhairul Izzreen; Abu Bakar, Mohd Fadzelly; Mohamad Razali, Umi Hartina; R., Rabiatul Amirah; Ashari, Rozzamri (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2020)
The present work investigated the cytotoxicity capacity of the MDA-MB-231 (human cancer-derived), A549 (human lung cancer-derived), Caov3 (human ovarian cancer-derived), and HeLa (human cervical cancer-derived) cell lines on a wide range of tea leaves; green tea, black tea, tea waste, and compost from Sabah. A group of male and female Sprague Dawley rats was used to screen the sub-acute toxicity of green tea extract in tea leaves from Sabah for 28 d. Results revealed that the ethanol extract of tea leaves had strong cytotoxic activity against all cancer lines. Tea waste showed higher cytotoxicity when extracted using hot water. The ethanol extract of black tea leaves exhibited the highest inhibitory activity against the proliferation of Caov3, whereas the ethanol extract of green tea leaves exhibited a promising cytotoxic activity against MDA-MB-231 and HeLa cell lines. Toxicity studies showed decreased testes weight and increased liver weight in male rats that were administered with 5000 mg/kg of tea extract. This coincided with the significant increase portrayed by enzyme alanine aminotransferase (ALT) in the serum of treated male rats in the 5000 mg/kg dose group. Moreover, there was an increase of alkaline phosphatase (ALP) and ALT for the female rats in the 5000 mg/kg dose group. The increased levels of ALT and ALP enzymes, as well as liver weight, signified mechanical trauma in the liver of male and female rats in the 5000 mg/kg dose group.